E-test versus agar dilution for antibiotic susceptibility testing of Helicobacter pylori: A comparison study - Muhammad Miftahussurur (BioMed Central Ltd., 2020)
Objective: For evaluating the antibiotic resistance of Helicobacter pylori, the agar dilution method is the gold standard; however, using this method in daily practice is laborious. E-test has been proposed to be an uncomplicated method. This study was aimed at validating the E-test and detecting the presence of any bias between the agar dilution method and E-test. Results: The agar dilution method and E-test were performed using five antibiotics for 72 strains of H. pylori obtained from clinical patients in Indonesia. The E-test's results showed a higher prevalence of resistance to all the antibiotics tested but the difference was not significant. Results showed high essential agreement (> 90.0) for all the antibiotics, but only 84.7 for metronidazole. The agreement for MIC value was acceptable for levofloxacin, clarithromycin, and metronidazole. For amoxicillin, it showed only fair agreement (0.25) by the Kappa analysis and significant difference by Passing-Bablok regression. Even though some discrepancies were found, the E-test has an acceptable agreement for levofloxacin, metronidazole, tetracycline, and clarithromycin but further confirmation may be necessary for amoxicillin. Â© 2020 The Author(s).